Conflict management of Lake Toba halal tourism planning in the perspective of organisational communication - Safitri, Lies Utami Efni (Jurnal Studi Komunikasi, 2021)
The issue of planning for halal tourism in Lake Toba is controversial, in the form of rejection from residents around the Lake Toba area, this is due to two factors; namely, the issue of halal tourism is considered to threaten the cultural existence of the Batak people and the threat of Islamisation through the medium of halal tourism. This tension requires local governments to take conflict management steps following the existing historical, social context. This study uses an organisational communication perspective to describe the conflicts that occur. This study's findings are that the local government of North Sumatra has not optimally used an organisational communication approach involving all cultural-based community organisations to formulate a mutual agreement regarding halal tourism plans in Lake Toba.